KINERJA STASIUN KERETA API LUBUK LINGGAU - Erika Buchari (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2010)
According to Law Number 23 of 2007, on Railways, the train station for loading and unloading of goods shall be equipped with safety, security, loading and unloading goods, and public facilities. The condition of the railway station in Lubuk Linggau, South Sumatra, is now very crowded, with spaces for vehicle parking shuttle and for loading and unloading of goods are no longer sufficient, thus affecting the performance of this station. The data indicate that the modes of transport used by passengers using the railway mode for Palembang-Lubuk Linggau or vice versa are motorcycles, paratransit, private car, which require facilities to intermodal transfer. The transport of goods shows that those with two trips, which indicate the existence of a distribution of goods in the town of Lubuk Linggau, are about 7.6%. This means that loading and unloading facilities at the station are needed. To improve its performance, in Lubuk Linggau station must be equippedwith the facilities in accordance with existing regulations.Keywords: railway station performance, passenger transport, cargo transport, intermodal transfer